Chapter 28 Agreement - Corbett, Greville G. (De Gruyter, 2009)
In many respects the agreement systems of Slavonic languages are close to canonical. Controllers of agreement are often present, they have overt expression of features, and they take consistent agreements. The target has obligatory bound expression of agreement, and there is matching of features values (for person, number and gender). How-ever, Slavonic also shows several very interesting instances of agreement choices, induced by a range of different controller types. These agreement choices provide good evidence for the constraints of the Agreement Hierarchy and the Predicate Hierarchy, as well as for various types of condition on agreement, notably animacy and precedence.